Air pollution and incidence of cancers of the stomach and the upper aerodigestive tract in the European Study of Cohorts for Air Pollution Effects (ESCAPE). Issue 7 (3rd July 2018) - Nagel, Gabriele; Stafoggia, Massimo; Pedersen, Marie; Andersen, Zorana J; Galassi, Claudia; Munkenast, Jule; Jaensch, Andrea; Sommar, Johan; Forsberg, Bertil; Olsson, David; Oftedal, Bente; Krog, Norun H; et al.
Abstract : Air pollution has been classified as carcinogenic to humans. However, to date little is known about the relevance for cancers of the stomach and upper aerodigestive tract (UADT). We investigated the association of long‐term exposure to ambient air pollution with incidence of gastric and UADT cancer in 11 European cohorts. Air pollution exposure was assigned by land‐use regression models for particulate matter (PM) below 10 µm (PM10 ), below 2.5 µm (PM2.5 ), between 2.5 and 10 µm (PMcoarse ), PM2.5 absorbance and nitrogen oxides (NO2 and NOX ) as well as approximated by traffic indicators. Cox regression models with adjustment for potential confounders were used for cohort‐specific analyses. Combined estimates were determined with random effects meta‐analyses. During average follow‐up of 14.1 years of 305, 551 individuals, 744 incident cases of gastric cancer and 933 of UADT cancer occurred. The hazard ratio for an increase of 5 µg/m 3 of PM2.5 was 1.38 (95% CI 0.99; 1.92) for gastric and 1.05 (95% CI 0.62; 1.77) for UADT cancers. No associations were found for any of the other exposures considered. Adjustment for additional confounders and restriction to study participants with stable addresses did not influence markedly the effect estimate for PM2.5 and gastric cancer. Higher estimated risks of gastric cancer associated with PM2.5 was found in men (HR 1.98 [1.30; 3.01]) as compared to women (HR 0.85 [0.5; 1.45]). This large multicentre cohort study shows an association between long‐term exposure to PM2.5 and gastric cancer, but not UADT cancers, suggesting that air pollution may contribute to gastric cancer risk. Abstract : What's new? To date little is known about the relevance of long‐term air pollution for cancers of the stomach and upper aerodigestive tract (UADT). Here the authors performed a multicenter cohort study including more than 300, 000 individuals and found an association between long‐term exposure to particular matter with less than 2.5 micrometers in diameter and gastric cancer risk. No increased risk was found for cancers of the UADT, pointing to a specific connection between air pollution and stomach cancer.